DERAJAT SUMBATAN HIDUNG PADA SEPTUM DEVIASI DAN KONKA HIPERTROFI - MUHAMMAD FIKRI; SITI MASLIANA SIREGAR (JURNAL ILMIAH KOHESI, 2020)
Nasal obstruction will distraction with air flow to the nose. Nasal obstruction is indeed not a severe disease, but the symptoms of nasal obstruction itself can interfere with patient activity and can reduce the quality of life of patients. The causes of nasal obstruction itself can be various, namely septal deviation, Concha hypertrophy, allergic rhinitis, polyps, and others. The nasal septal deviation is the shape of the uneven septum which forms a deviation of the nasal septum to one side of the nasal cavity. This, of course, will cause interference on one side of the nose. Concha hypertrophy is an increase in concha cell size which will cause enlargement of the turbinate tissue. The aim of the study was to look at the overview of nasal obstruction in the septal deviation, concha hypertrophy and septum deviation with turbinate hypertrophy. This type of research is an observational descriptive study with a cross-sectional design. The subjects in this study were all patients with turbinate hypertrophy and septal deviation in the ENT polyclinic of Medan TK-II Bhayangkara Hospital and Dr. Pringadi General Hospital Medan in October to December 2018 which numbered 27 people. This research technique uses total sampling. Retrieving data through filling in questionnaires. The results of the study were a nasal obstruction in septum deviation patients and hypertrophic turbinate measured using the SNOT-22 questionnaire, TNSS questionnaire, and NOSE questionnaire. Based on the SNOT-22 questionnaire, the most reported degree of nasal obstruction was a moderate blockage, namely 21 patients (77.8%). Based on the TNSS questionnaire, the most reported degree of nasal obstruction was a mild degree of obstruction of 15 patients (55.6%). Based on the NOSE questionnaire, the most reported degree of nasal obstruction was a significant degree of obstruction, 13 patients (48.1%). This shows that the SNOT-22 questionnaire, TNSS Questionnaire, and NOSE Questionnaire can be used to measure nasal obstruction in patients with septal deviation and hypertrophic turbinate. There is a nasal obstruction in patients with septal deviation and hypertrophic turbinate.